Internationalization of Renminbi as A Response of China's Economic Development - Hilyatu Millati Rusdiyah; Ahmad Syaifuddin Zuhri (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
This paper is aimed to study the internationalization of Renminbi as the ambition of China in supporting its economic rapid development. Over the last few years, use of Renminbi for international trade has been growing steadily. The use of Renminbi by more countries encourage Renminbi to be involved in International currency basket. The internationalization of a currency should match with a country’s economic status in the global economy. It’s depend on growth rate of country’s economic rather than external pressures. After the joining Renminbi in the international currency basket, the question arises will China’s economy maintain its development despite its growth rate experiencing the decreasing trend in recent years? Meanwhile, the internationalization of Renminbi provides benefits and raises political concern. The benefits for ASEAN countries, will eliminate the additional cost and exchange rate risk. But the joining of Renminbi in international currency basket raises political concern will affect to the ability of West in imposing economic sanctions and enhance China’s political influence. Keywords: Internationalization, Renminbi, Economic, China